Influence of nitrogen, Azospirillum sp. and farmyard manure on growth, yield and inci- dence of stem gall disease in coriander (Coriandrum sativum L.) - V V Apparao, S K Malhotra, B B Vashishtha (Journal of Spices and Aromatic Crops, 2006)
The influence of Azospirillum sp. (biofertilizer), nitrogen fertilizer, farmyard manure and theircombinations on coriander (Coriandrum sativum), was studied at Ajmer (Rajasthan).Azospirillum sp. inoculation along with nitrogen and farmyard manure increased plant heightand number of primary branches plant-1 as compared to Azospirillum sp. alone and absolutecontrol. Number of umbels plant-1 and number of grains umbel-1 increased significantlywhen Azospirillum sp. was applied in combination with 100% nitrogen + 5 t farmyard ma-nure, 75% nitrogen + 5 t farmyard manure and 50% nitrogen + 5 t farmyard manure ha-1.Higher seed yield was recorded in Azospirillum sp. + 100% nitrogen + 5 t farmyard manure(10.8 q ha-1) followed by Azospirillum sp. + 75% nitrogen + 5 t farmyard manure (10.2 q ha-1)and Azospirillum sp. + 50% nitrogen + 5 t farmyard manure ha-1 (9.7 qha-1). The use ofAzospirillum sp. + 50% nitrogen + 5 t farmyard manure ha-1 was the most economical treat-ment for obtaining higher seed yield. The Azospirillum sp. treatment combinations also re-duced the incidence of the seed-borne stem gall disease of coriander.